Pengaruh Bauran Pemasaran Sumber Daya Manusia (SDM) terhadap Loyalitas Pasien Rumah Sakit: Systematic Review - Primasari, Elsa (UI Scholars Hub, 2021)
In today's fast-paced era of information and technology, there is also a demand for advancements in healthcare services, particularly hospitals. Currently, more and more hospitals are being established in Indonesia, resulting in increased competition among them. Therefore, hospitals must innovate by utilizing the marketing mix, especially the human resources factor, to maintain patient loyalty. This article aims to determine the influence of the human resources marketing mix on patient loyalty in hospitals. This study uses a systematic review design. The search was conducted using the keywords